The Relationships Between Leadership Effectiveness and Competitiveness of Small- and Medium-Sized Enterprises in Chiang Mai Province - Tarasueb, Nut; Pansuwan, Boonchan (Journal of Public Administration Chiang Rai Rajabhat University, 2019)
The objectives of this research were to study 1) the leader effectiveness of small- and medium-sized enterprises in Chiang Mai province 2) the competitiveness of SMEs in Chiang Mai, and 3) the relationship between the effectiveness of SME leaders and the competitiveness of SMEs in Chiang Mai. The sample group used in this research consisted of 400 SME administrators who were juristic persons. The questionnaire was used as a tool to collect data. The validity of the questionnaire was 0.68 - 1.00 and the reliability of the questionnaire was 0.97. [The data were analyzed by means of] structural equation analysis The results of the research revealed that 1) the analysis of the opinion toward leader effectiveness was at a high level. 2) the analysis of the opinion toward competitiveness was at a high level. 3) the analysis of the relationship between the effectiveness of SME leaders and the competitiveness of SMEs showed that the leader effectiveness had the same relationship with the competitiveness at the coefficient level of 1.31 and the significance level of 0.01.